Mortality of early treatment for radiation-induced brain necrosis in head and neck cancer survivors: A multicentre, retrospective, registry-based cohort study - Dong Pan; Xiaoming Rong; Dongping Chen; Jingru Jiang; Wai Tong Ng; Haiqiang Mai; Yi Li; Honghong Li; Jinhua Cai; Jinping Cheng; Yongteng Xu; Melvin Lee Kiang Chua; et al. (EClinicalMedicine, 2022)
Summary: Background: The evidence of early treatment for radiation-induced brain necrosis (RN) in head and neck cancer survivors remains insufficient. This study aimed to determine whether early anti-RN treatment was associated with lower mortality. Methods: In this cohort study, we utilized data from the Study in Radiotherapy-related Nervous System Complications (NCT03908502) and Hong Kong Cancer Registry. We included consecutive patients who had received radiotherapy (RT) for head and neck cancers and had subsequently developed RN between Jan 8, 2005 and Jan 19, 2020. Patients who had tumor progression before the diagnosis of RN, underwent surgical brain necrosis lesions resection before corticosteroids and/or bevacizumab treatment, had intracranial metastases before the diagnosis of RN, lacked follow-up data, or had a follow-up period of less than three months were excluded. Individual-level data were extracted from electronic medical records of the above-mentioned registries. The primary outcome was all-cause death. The vital status of each patient was confirmed through a standardized telephone interview. We compared patients who received early treatment (initiating bevacizumab or corticosteroids treatment within three months after RN diagnosis) with patients who did not (following a “watch-and-wait” policy). Findings: Of 641 eligible patients, 451 patients (70·4%) received early treatment after RN diagnosis and 190 patients (29·6%) did not. Overall, 112 patients (17·5%) died, of whom 73 (16·2%) in the early treatment group and 39 (20·5%) in the watch-and-wait group, during a median follow-up of 3·87 years. The early treatment group showed a lower risk of all-cause death compared with the watch-and-wait group after adjusting for age, sex, absence or presence of neurological symptoms at baseline, RN lesion features on brain magnetic resonance imaging, history of stroke, prior tumor-related characteristics (TNM stage, RT dose and techniques, and chemotherapy), and the time interval from RT to RN (HR 0·48, 95%CI 0·30 to 0·77; p = 0·0027), and extensive sensitivity analyses yielded similar results. There was no significant difference in the effect of early treatment on post-RN survival among subgroups stratified by presence or absence of neurological symptoms at diagnosis (p for interaction=0·41). Interpretation: Among head and neck cancer survivors with RN, initiating treatment early after RN diagnosis is associated with a lower risk of all-cause mortality as compared with following the watch-and-wait policy, irrespective of whether patients exhibit symptoms or not. Further prospective randomised studies would be needed to validate our findings since the observational study design might lead to some potential confounding. In the absence of data from randomised trials, our study will have an important implication for clinicians regarding the optimal timing of treatment for RN, and provides the foundation and supporting data for future trials on this topic. Funding: National Natural Science Foundation of China (81925031, 81820108026, 81872549, 81801229, 82003389), the Science and Technology Program of Guangzhou (202007030001), Young Teacher Training Program of Sun Yat-sen University (20ykpy106), Key-Area Research and Development Program of Guangdong Province (2018B030340001), the National Medical Research Council Singapore Clinician Scientist Award (NMRC/CSA-INV/0027/2018, CSAINV20nov-0021), the Duke-NUS Oncology Academic Program Goh Foundation Proton Research Programme, NCCS Cancer Fund, the Kua Hong Pak Head and Neck Cancer Research Programme, and the National Research Foundation Clinical Research Programme Grant (NRF-CRP17-2017-05).